Kajian Potensi Interaksi Obat Antihipertensi pada Pasien Rawat Jalan di RS Bhayangkara Kupang - Sindy Nau; Magdarita Riwu; Nurul F. Pua Upa (LPPM Universitas Abdurrab, 2026)
Hypertension requires long term therapy that often involves drug combinations, thereby increasing risk of drug interactions that may affect effectiveness and safety of treatment. This study aimed to evaluate potential for antihypertensive drug interactions among outpatients at Bhayangkara Hospital Kupang from January to June 2025, based on severity levels and interaction mechanisms. This was a descriptive retrospective study utilizing patient prescription data. A total sampling technique was applied, obtaining 300 prescriptions that met inclusion and exclusion criteria. Potential drug interactions were screened using Medscape Drug Interaction Checker and Drugs.com, followed by descriptive analysis. Results showed that out of 300 prescriptions, 205 (68.33%) had potential drug interactions. Amlodipine was most frequently prescribed drug (52.56%). A total of 412 cases of potential drug interactions were identified, which were dominated by moderate severity with 322 cases (78.15%), followed by major severity with 47 cases (11.41%), and minor severity with 43 cases (10.44%). Based on mechanism, pharmacodynamic interactions were most dominant with 336 cases (81.55%), while pharmacokinetic interactions accounted for 76 cases (18.45%). In conclusion, the potential for antihypertensive drug interactions at Bhayangkara Hospital Kupang remains high, predominantly characterized by moderate severity and pharmacodynamic mechanisms. Optimal therapeutic monitoring is essential to enhance patient safety.